PSVIII-30 Relationship of molecular breeding value for beef tenderness on heifer traits through weaning their first calf. (5th December 2019) - Bennett, Gary L; Cushman, Robert; McNeel, Anthony K; Casas, Eduardo; Smith, Timothy P
Abstract: Selection for beef carcass traits using SNP may have off-target effects on reproduction. Composite cattle (MARC III) were selected for SNP affecting beef tenderness. Selection increased minor allele frequency of a polymorphism in calpastatin (CAST) and changed frequencies of three common haplotypes in µ-calpain (CAPN1) towards 0.33 resulting in heifers of all 18 (3 CAST × 6 CAPN1) genotypes. The minor allele frequency for a diacylglycerol O-acyltransferase 1 (DGAT1) polymorphism was also increased but was not expected to affect beef tenderness. About 60 heifers were retained over 3 years (N = 187). Retention was based on representing the entire genotypic distribution. Contemporary steers from the population were harvested and measured for meat tenderness using slice shear force. Steer data were used to predict molecular breeding values (MBVSSF; 0.0 to 4.1 kg) for the heifers based on CAST and CAPN1. Traits were analyzed with linear covariates for MBVSSF and number of DGAT1 K alleles (0, 1, or 2), fixed effects appropriate for the trait, and random sire of heifer effects. A 1.0 kg increase in heifer MBVSSF was associated (P ≤ 0.05) with 5.6 ± 2.8 d earlier puberty and a 0.73 ± 0.36 kg increase in birth weight of their first calf. Pregnancy rates were not affected but would have had to exceed 5 to 6 % per kg MBVSSF to be significant. A larger experiment would be needed to detect differences that are smaller but still economically important. Regression coefficients for DGAT1 were significant for pre-calving hip height (0.78 ± 0.37 cm) and 26-mo weight (7.2 ± 3.6 kg). Within the precision of this experiment, selecting for more tender MBVSSF or for DGAT1 appears to have little negative effect on economically important traits in heifers but may increase age at puberty. USDA is an equal opportunity provider and employer.